Oxygen-induced faults in bottled white wine: A review of technological and chemical characteristics. (30th June 2021) - Gabrielli, Mario; Fracassetti, Daniela; Romanini, Elia; Colangelo, Donato; Tirelli, Antonio; Lambri, Milena
Graphical abstract: Highlights: Premature wine oxidation causes a quick decay of bottled wine with aging potential. Changes in the oxidative status are affected by both oxygen and storage conditions. Wine-bottle-closure system plays a consistent effect. Alteration of color to yellow-brownish or even pinking hues can occur. Aroma losses and off-flavor formation are associated to this phenomenon. Abstract: Several changes can take place in wine after blotting. Some of them lead to the desired evolution of wine being more complex, round and pleasant. However, unexpected changes can also occur ascribable to the premature wine oxidation (PremOx) arising when a wine, presumably with aging potential, results oxidized and often undrinkable. The complexity of PremOx, where aromas are also involved, makes difficult to identify all the oxidation products, and to predict its occurrence in wines. Despite most studies have been focused on the effect of time after wine bottling on PremOx as well as pinking phenomena, identification of pinking markers, reliable methods for their detection in wine, and correlations between markers and the wine-bottle-closure system are still unknown. This review aimed to highlight aspects PremOx-related, including wine-bottle-closure system, color change, with particular emphasis on pinking, and aroma decay based on the current knowledge becoming the bases for future perspectives.